Design of intelligent miner's lamp charging monitoring and management system - ZHANG Faquan; FENG Shuai; XIAO Hailin; YE Jincai; WANG Guofu (Gong-kuang zidonghua, 2017)
In view of problems of poor extensibility, single communication mode and difficult locating of fault point existed in current miner's lamp charging monitoring and management system, an intelligent miner's lamp charging monitoring and management system was designed. In the system, charging unit collects miner's lamp condition in real-time, control unit receives the collected data through RS485 bus and transmits it to CAN/Ethernet module through CAN bus, server receives the data through Ethernet,monitoring software displays charging condition according to the data uploaded by the server and sends miner's information to the charging unit. The test results show that the system can accurately collectminer's lamp condition and realize real-time miner's lamp monitoring and miner's information management.